Induction of cellular DNA synthesis by a simian virus 40 mutant defective in nuclear transport of T antigen. - Lanford, R E (1985)
The simian virus 40 (SV40) (cT)-3 mutant [SV40(cT)-3], which is defective in nuclear transport of T antigen, was utilized to determine whether cellular DNA synthesis can be stimulated by SV40 in the absence of detectable nuclear T antigen. Cellular DNA synthesis was examined in the temperature-sensitive cell cycle mutants, BHK ts13 and BHK tsAF8, after microinjection of quiescent cells with plasmid DNA containing cloned copies of wild-type SV40 or SV40(cT)-3. The efficiency of induction of cellular DNA synthesis was identical for both wild-type SV40 and SV40(cT)-3 in both cell lines. The results suggest that cell surface-associated T antigen, either alone or possibly in combination with minimal amounts of nuclear T antigen below our limit of detection, is able to stimulate cellular DNA synthesis.